Investigation of CNC turning parameters by using a vortex tube cooling system - (:unkn) unknown (Polish Academy of Sciences, 2015)
Controlling the heat, generated during the cutting process, is an important factor in improving the quality of the product and performance of the machining. A vortex tube was employed to evaluate the effects of cooling on the turning parameters. Various cutting parameters (100 m/min, 250 m/min and 400 m/min) together with various cooling temperatures (-4 °C, 8 °C and 20 °C) were considered to find surface roughness, cutting force and cutting temperature. Response surface methodology was used to optimize the experimental parameters. The best attainable surface roughness value was found to be 0.77 μm Ra, under the conditions of 0.15 mm/rev feed, 400 m/min cutting speed, -4 °C (with vortex tube) cutting temperature and 1.2 mm tool edge radius. Cutting forces were not affected by the temperature changes. The difference was negligible and as small as 1%. The minimum cutting temperature was 74.17 °C, which was obtained under the machining conditions of 0.25 mm feed, 250 m/min cutting speed -4 °C (with vortex tube) cutting temperature and 0.8 mm tool edge radius.